2008
DOI: 10.1007/s00421-008-0854-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bed rest and an exercise countermeasure on leg venous function

Abstract: This study was performed to assess the effect of resistive vibration exercise during bed rest deconditioning on venous vascular dimension and function, as measured with ultrasound in the popliteal vein. Sixteen men were assigned to bed rest (BR-Ctrl) or bed rest with resistive vibration exercise (BR-RVE). Before and at 25 and 52 days of bed rest, popliteal vein diameter was measured at increasing cuff pressures. Venous capacitance and compliance were calculated from the pressure-volume curve. After 52 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…However, the exercise intervention failed to prevent an exaggeration of the vasodilation in response to flow or to nitroglycerine (Bleeker et al 2005), which both are mediated by nitric oxide. Finally, resistive vibration training likewise failed to prevent decreases in popliteal vein capacitance (van Duijnhoven et al 2008), suggesting that the training modality may not fully safeguard orthostatic tolerance.…”
Section: Bed Rest Studiesmentioning
confidence: 97%
“…However, the exercise intervention failed to prevent an exaggeration of the vasodilation in response to flow or to nitroglycerine (Bleeker et al 2005), which both are mediated by nitric oxide. Finally, resistive vibration training likewise failed to prevent decreases in popliteal vein capacitance (van Duijnhoven et al 2008), suggesting that the training modality may not fully safeguard orthostatic tolerance.…”
Section: Bed Rest Studiesmentioning
confidence: 97%
“…Immobilization, as tested in bed rest studies, demonstrated a significant decline in venous capacitance after 52 days, which was not affected by resistive vibration exercise. 187 Venous compliance remained unaffected.…”
Section: Venous Circulationmentioning
confidence: 97%
“…21 Moreover, others found that vibration exercise involving a resistive component at least partly prevents detrimental changes in vascular function 4,22 and structure. 4,22,23 However, no previous studies have examined the potential of exercise countermeasures to prevent changes in artery wall characteristics associated with chronic bed rest. To examine this, we assessed the impact of countermeasures involving resistive exercise alone, or in combination with vibration, on carotid and superficial femoral arterial wall thickness and wall:lumen ratio before and after 60 days of bed rest in healthy, young volunteers.…”
mentioning
confidence: 99%